Lipoid Proteinosis: A Rare Disease In Pediatric Dentistry - Lourenço,Alan Grupioni (2020)
Abstract This report describes the diagnostic process of a rare disorder in a Brazilian female child. The patient presented initially as a 7-year-old with multiple whitish submucosal nodules of a fibrous consistency in the lower lip, but with an inconclusive pathology report. When she turned 9 years of age, she presented with exacerbation of the original clinical findings, which then involved the upper lip, buccal mucosa, tongue and lingual frenulum. In addition, dermatological lesions were noted on the child’s limbs and face, as well as a hoarse voice. Histopathological examination of the buccal mucosa revealed dense connective tissue with hyaline foci, which were positive with periodic acid-Schiff (PAS) staining and resistant to diastase digestion. Clinical and histopathological findings led to the diagnosis of a rare genetic disease with fewer than 300 reported cases - lipoid proteinosis. Magnetic resonance imaging revealed calcium deposits in her amygdaloid region of the brain, and nasopharyngolaryngoscopy revealed lesions in her vocal cords. The patient currently is stable and under multidisciplinary follow-up, but no treatment has been recommended to date.